Safety of machinery. Electro-sensitive protective equipment. Particular requirements for equipment using vision based protective devices (VBPD). Additional requirements when using stereo vision techniques (VBPDST) Part 4-3, (31st May 2015) - British Standards Institution,
No abstract available